The Methods of Assertion in the Tafsīr Abi al-Sa'ud - Khan, Yahya; Hafiz Ullah (Journal of Islamic and Religious Studies, 2018)
The concept of assertion has been playing a vital role in the linguistic to specify the meaning and nullify the uncertainties from the sentences. The numerous uses of assertion and its tools in Arabic language also played very significant role in interpreting the Qur’ān. Due to this reason rhetoricians and exegetists have much emphasized this phenomenon in their books and exegesis. One of the renowned books written by Abdul Qahir Jurjani is "دلائل الإعجاز" in which he mentioned its importance, principals and components in detail. The aim of this paper is to investigate the methods and stratigeis used by the great Muffasīr Abu Sa'ud, who tried to apply the rhetoric principals in his Tafsīr "إرشاد العقل السليم إلي مزايا القرآن الكريم" more emphasizing the phenomenon of assertion, its components, tools and importance in molding the concepts and meaning of the sentence.